BIOKONVERSI LIMBAH PERTANIAN MENJADI BIOPESTISIDA RIZOBAKTERI ANTIFUNGAL - Selviana Anggraini; Sri Murtini; Indri Vajry; Poppy Khairunnisa; Paisal Ansiska (University of Prof. Dr. Hazairin, SH, 2025)
Modern agriculture faces increasing challenges from soil-borne fungal pathogens such as Fusarium oxysporum, Rhizoctonia solani, and Sclerotium rolfsii, which cause severe root and wilt diseases and significantly reduce crop productivity. This study employed a qualitative–descriptive approach supported by controlled laboratory experiments to evaluate the potential of agricultural waste as an alternative, low-cost substrate for producing antifungal rhizobacterial biopesticides. Six types of agricultural waste—rice straw, rice husk, corn cob, sugarcane bagasse, coffee husk, and soybean residue—were assessed based on their C/N ratio, lignin content, biodegradability, and nutrient availability. The results indicated that substrates with moderate C/N ratios (15–25) and low lignin content, particularly soybean residue and sugarcane bagasse, promoted optimal rhizobacterial colonization, robust biofilm formation, and high production of antifungal metabolites such as chitinase and siderophores. Rhizobacteria cultured on soybean residue exhibited the strongest inhibition zone against Fusarium oxysporum (20.5 mm) and the highest plant protection efficacy (88%), with biopesticide stability maintained for up to 120 days. Two conceptual models, Substrate Structure Colonization (SSC) and Media Metabolite Effectiveness (MME), are proposed to explain the relationship between substrate structure, metabolite biosynthesis, and biopesticide performance. These findings provide a sustainable strategy for converting agricultural waste into high-value bio-based inputs, supporting circular economy practices and green agriculture initiatives.